How does energy matter? Rural electrification, entrepreneurship, and community development in Kenya - VERNET, Antoine (Institutional Knowledge at Singapore Management University, 2019)
We examine the impact of rural electrification on individuals and businesses within a community in order to test a resource-based theory of entrepreneurship. We show that access to electricity increases average households’ income and entrepreneurial activities. The impact of electricity on entrepreneurial activity has wide-ranging implications for development policy in countries where access to electricity is sparse. Results show a significant difference in entrepreneurial opportunities with respect to firm formation, with the electrified site reporting more new micro-enterprises than the control site after implementation. Electrification affects both households’ income, individuals’ perceptions of their social position, and opportunities for business development. Individuals’ future expectations and entrepreneurial activities are enhanced in the community that receives electricity. We also find evidence that women-led households benefit from electrification more than men-led ones, but this benefit does not eliminate the difference in income between women and men-led household. We discuss implications of the study for entrepreneurship and community social development interventions.